PROFILE OF MIO-ARTICULARES CHANGES ON HUMANS RESOURCES DEPARTMENT EMPLOYEES OF COMPANY APPLE'S SECTION OF FRAIBURGO'S CITY (SC). (Fiep Bulletin - online, 2014)
INTRODUCION: The muscle-skeletal disturbances are affections that could attack muscles, tendons and bags articulate, reaching principally the superior members, scapular region and neck. They occur on jobs where there are continued and repeated movements and maintenance of inadequate postures, without viable time for the recovery of the requested muscle. OBJECTIVE: The present study search verify the incidence, the symptomatology and the anatomics regions more assaulted, beyond the main positions and movements adopted during the hours of working and the index of absenteeism provoked by muscle-skeletal disturbances on humans resources department employees. METHODS: The data were collected through a questionary, formulated based on instruments utilized by Massambani and Pereira. Also utilized the Scala CR10 de Borg to measure the pain level. These instruments were applied on 9 company, totalize 46 individuals that working on that place. RESULTS: Through the data obtained we can conclude that the incidence of mio-articulares chances was 15,56%, with prevalence on class feminine (57,14%). The anatomics regions more affected were: fist, hands, shoulder, neck and lumbar column. The principal symptoms include: burning, fatigue and pulsate pain, that are feeling principally in the final of the expedient. The principal changes on the conduct of employees are: anxiety, physical fatigue, irritation and nervousness, and the most doesn't pratice any type of physical activity. The level of pain measure in the subjects varies of absolutely nothing to pain level 6. The main positions and movements that occur during the work are: repetitive movements with fist and hands, rotation of seated trunk, support of elbow in the table, flexion of the neck, use of manual techniques and maintenance of static position for long periods. The index of absenteeism was zero. CONCLUSION: However, looks opportune to establish preventive measure like stretch break and ergonomic analysis of working places, besides to minimize the fortuitous problems surged by labor activity.
Keywords: Mio-Articulares Chances; Humans Resources Department; Apple's Company